The basic solar wind speed distribution and its sunspot cycle variations - Akasofu, Syun-Ichi; Lee, Lou-Chuang (Frontiers in Astronomy and Space Sciences, 2023)
In this paper, it is suggested that the latitudinal solar wind speed observed by the Ulysses spacecraft during the lowest solar activity (when both the ecliptic and magnetic equators coincide) may be identified as the basic speed distribution throughout the solar cycle. We demonstrate this suggestion by rotating this particular Ulysses distribution counterclockwise up to 70 in accordance with the rotation of the equivalent dipole axis during active periods of the cycle. The corresponding magnetic equator in the Carrington map (latitude-longitude [27 days]) becomes quasi-sinusoidal with respect to the ecliptic equator. The quasi-sinusoidal magnetic equator on the Carrington map and its modification associated with the degree of sunspot activities can explain the two high speed peaks (750-800 km/s) and the two lowest speed (350 km/s) during 27-day solar rotation periods, most clearly recognizable after the sunspot peak period. Thus, it may be not necessary to consider coronal holes or open regions as the source of high speed streams. In fact, this particular (lowest solar activity) Ulysses distribution may represent the speed distribution pattern by the basic generation process of the solar wind itself.